16 nm-resolution lithography using ultra-small-gap bowtie apertures. (23rd December 2016) - Chen, Yang; Qin, Jin; Chen, Jianfeng; Zhang, Liang; Ma, Chengfu; Chu, Jiaru; Xu, Xianfan; Wang, Liang
Abstract: Photolithography has long been a critical technology for nanoscale manufacturing, especially in the semiconductor industry. However, the diffractive nature of light has limited the continuous advance of optical lithography resolution. To overcome this obstacle, near-field scanning optical lithography (NSOL) is an alternative low-cost technique, whose resolution is determined by the near-field localization that can be achieved. Here, we apply the newly-developed backside milling method to fabricate bowtie apertures with a sub-15 nm gap, which can substantially improve the resolution of NSOL. A highly confined electric near field is produced by localized surface plasmon excitation and nanofocusing of the closely-tapered gap. We show contact lithography results with a record 16 nm resolution (FWHM). This photolithography scheme promises potential applications in data storage, high-speed computation, energy harvesting, and other nanotechnology areas.